Pesticides, external costs and policy options for Thai agriculture - Suwanna Praneetvatakul (2018)
This study addresses the questions of how to estimate the external costs of agricultural pesticide use and how to disaggregate these costs to particular chemicals and farm production systems. Using the case of Thailand-a lower-middle income country with an export-oriented agriculture and an annual growth in pesticide use of about 10%, we estimate the external costs of pesticide use for the period 1997-2010 by applying the Pesticide Environmental Accounting (PEA) tool and compare the estimates to an accounting of actual costs for two years. We also use the tool to estimate the external costs of two distinct production systems of rice and intensive horticulture. Using the PEA tool, we estimate the average external costs of pesticide use in Thailand to be USD 27.1/ha of agricultural land in 2010; yet the actual cost estimate for the same year is only USD 18.7/ha. This difference leads us to discussing the strengths and weaknesses of the PEA approach. The negative externalities of pesticide use could be reduced by giving farmers a financial incentive to use fewer pesticides, for instance by introducing an environmental tax. We argue that for such instrument to be effective, it needs to be combined with supportive measures to change on-farm practices through awareness-raising about the adverse effects of pesticides and introducing farmers to non-chemical alternatives to manage their pest problems. © 2012 Elsevier Ltd.